How'm I doing? (Psychology Today)
Research by Penn State psychologist Kathryn Aikin suggests that when it comes to giving feedback, there may be no substitute for human touch. Aikin sent students on-line criticism of their performance in a game testing reasoning skills. Half the students were told that the computer provided the critiques, and the rest believed Aikin monitored their performance. She found that students were less likely to believe failure feedback when it came from a computer.